Tinjauan Literatur tentang Filsafat Pendidikan Islam: Relevansi dan Implementasi di Era Modern - Mujiburrohman, Mujiburrohman; Sayidah, Aminatus (TSAQOFAH, 2025)
Islamic educational philosophy is a conceptual framework that focuses on the intellectual, moral, and spiritual development of humans. In the modern era, characterized by the challenges of globalization and secularization, Islamic educational philosophy offers a holistic approach to shaping Muslim individuals with integrity. This study aims to explore the core principles of Islamic educational philosophy, including tauhid (monotheism), moral education (akhlak), and the comprehensiveness (syumuliyah) of Islam, while identifying the relevance and challenges of its implementation in the modern era. The research employs a literature review method with descriptive analysis of relevant journals and academic articles. The findings show that while the principles of Islamic education remain relevant, challenges such as cultural penetration and technological advancements require innovation in curriculum approaches and the prudent use of technology. This study emphasizes the importance of integrating Islamic values into modern education to shape an adaptive Muslim generation without losing its Islamic identity. This research is expected to serve as a guide for educators in addressing the dynamics of global education.